2013
DOI: 10.1128/mcb.01075-12
|View full text |Cite
|
Sign up to set email alerts
|

Defective Autophagy and mTORC1 Signaling in Myotubularin Null Mice

Abstract: Autophagy is a vesicular trafficking pathway that regulates the degradation of aggregated proteins and damaged organelles. Initiation of autophagy requires several multiprotein signaling complexes, such as the ULK1 kinase complex and the Vps34 lipid kinase complex, which generates phosphatidylinositol 3-phosphate [PtdIns(3)P] on the forming autophagosomal membrane. Alterations in autophagy have been reported for various diseases, including myopathies. Here we show that skeletal muscle autophagy is compromised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 63 publications
3
82
0
Order By: Relevance
“…Alternatively, defective autophagic and proteasomal degradation as well as upstream signaling events in MTM1-deficient mice were proposed to be the primary cause of the muscle pathology in XLCNM (Al-Qusairi, Prokic et al 2013;Fetalvero, Yu et al 2013), but will be discussed only briefly in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, defective autophagic and proteasomal degradation as well as upstream signaling events in MTM1-deficient mice were proposed to be the primary cause of the muscle pathology in XLCNM (Al-Qusairi, Prokic et al 2013;Fetalvero, Yu et al 2013), but will be discussed only briefly in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…1). [35][36][37] As excessive autophagy often leads to cell death, these enzymes function to inhibit the harmful hyperactivation of basal and stress-induced autophagy. Identified by the present study ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this proposal, defects in MTMR function are implicated in myotubular myopathy and Charcot-Marie-Tooth peripheral neuropathy, 34 2 groups of diseases that are related to defective autophagy. [36][37][38][39][40][41] In this study, we identified a small molecule, AUTEN-67, which impedes human MTMR14, and potently enhances the autophagic process in HeLa cells, isolated neurons and in vivo models, including Drospohila, zebrafish and mice. Administering AUTEN-67 led to life-span extension in Drosophila, and effectively protected neurons in primary cell cultures from undergoing oxidative-stress induced cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Other than RYR1, all of the known CNM-associated proteins have welldocumented functions in processes unrelated to the triad. For example, MTM1 has been implicated as a regulator of autophagy and of the desmin intermediate filament network [59][60][61]. In addition, loss of MTM1 in both zebrafish and mouse models is associated with alterations of the NMJ (see below) [62,63].…”
Section: How Is the Triad Involved?mentioning
confidence: 99%